Answer:
just plug in the a b c and d for r and wich ever one makes that equatio equal then it that on
Step-by-step explanation:
Answer:
Step-by-step explanation:
-1.5(4-R)=12 divide both sides by -1.5
4-R=12/-1.5 calculate
4-R= -8 subtract 4 from both sides
-R=-8-4 calculate
-R=-12 multiply by -1
R=12
A spring balance measures?
Answer:
A spring balance measures the weight of an object by opposing the force of gravity acting with the force of an extended spring.
mrk brainliest?
I ordered 8 pizzas for my son’s birthday party. Each pizza had 8 slices. If my son and his friends ate 47 slices of pizza at the party, how many slices will I have leftover?
Answer:
17
Step-by-step explanation:
8*8 = 64
64 - 47 = 17
What is the x-coordinate in the solution of the system of equations y =
=-
I and 42
9y= -402
help plzzzzzz!!! The ratio of green marbles to total marbles in a bag is 2:9. The ratio of red marbles to total marbles in the same bag is 1:3. Which of the following statements is true?
There are more red marbles in the bag.
There are more green marbles in the bag.
There is the same number of red and green marbles in the bag.
Answer:
There are more red marbles in the bag
Step-by-step explanation:
2/9 = .2222 green
1/3 = .33333 red
Which of the following is true about a linear function? (4 points)
A. It may curve in some parts and be horizontal in others.
B. It must cross the origin.
C. It has a constant rate of change.
D. It must contain only positive values.
Answer:
The answer is c
Step-by-step explanation:
Answer:
the answer is C. It has a constant rate of change.
Step-by-step explanation:
i need help with this ^
What is 24 + x = 29?
Answer:
The answer is x=5
Step-by-step explanation:
hope this helps
Given:24 + x = 29
Solutions: To find the x subtract both side by 24.
24-24 + x = 29-24
x=5
Answer:
x=5
Step-by-step explanation:
24+x=29 - subtract 24 from both sides to isolate variable
x=5
Y=2/3x+5
Y=x+3
How do I solve for x I’m confused with the fraction part ?
Answer:
(6,9)
Step-by-step explanation:
Y=2/3x+5
Y=x+3
2/4x + 5 = x + 3
Solve the equation
x=6
Substitute the value of x
y=6+3
Solve the equation again.
Now we know y=9
(x,y) = (6,9)
Check the solution
9=2/3 x 6 + 5
9=6+3
Simplify
for his phone service, Jonh pays a monthly fee of $30, and he pays and additional $0.05 per minute of use. the least he has been charged in a month is $99.45
what are the possible number of minutes he has used his phone in a month?
use m for the numbers of minutes, and solve your inequality for m.
Answer:
m= 1395
Step-by-step explanation:
99.45 -30=
69.45
69.45 divided by 0.05
select the appropriate linear model for the scatter plot
The equation that best suits the scatter plot is y = x - 0.5.
A straight line graph has the general equation; y = mx + c Where; m = slope, c = y- intercept. We now have to examine each of the equations as written so as to determine which of the equations that best suits the scatter plot as shown.
First of all, we can see that the line did not start from origin. Looking at the graph very closely, we can conclude that the equation that best suits the scatter plot is y = x - 0.5.
Learn more: https://brainly.com/question/165414
Write a linear function f with f(0) = 7 and f(3) = 1.
f(x) = 0
A teacher grades 27 tests in 3 hours How many tests can the teacher grade in 8 hours if he works at the same rate
Answer:
72 tests
Step-by-step explanation:
lets put this in a ratio
27 (tests) : 3 (hours)
now we simplify by dividing each side by 3
9:1
Now we must find 8 hours so multiply each side by 8
72:8
the teacher will grade 72 tests in 8 hours
Can somebody help me on this
-(-3 / -2)= ???? I need help pleasee
Answer: -(-3 / -2)= ?
Step-by-step explanation:
Answer:
1.5
Step-by-step explanation:
- - = +
so 3 ÷ 2 is 1.5
hope it helps!
barb exercises for 22 hours each week. how many hours does she exercise in 14 weeks. use the array drawn on the grid go help multiply
Answer:
308 hours
Step-by-step explanation:
22 x 13
What is the domain and range of each relation
Answer:
1 ans
domain=(-2,0,2,4)
range=(-3,-1,0)
2 ans
domain=(-3,-1,0,3)
range=(-1,0,1,2,3)
Step-by-step explanation:
Bernardo is converting a fraction A/B, to a percent. Both A and B are whold numbers and not equal to zero. Which expression represents the percent?
A. (A÷B)÷100
B. (B÷A)÷100
C. 100(A÷B)
D. 100(B÷A)
Answer: I think that the answer might be C but I am not fully sure so please double check.
Have a fantastic day!
So sorry that I answered you late by the way.
Anwser:
C
Step-by-step explanation:because you multiply and you don’t multiply a upside down fraction so it is 100(A divided by B)
Find the distance between (3,9)and (0,5)
(3,4)
because I know it's right trust me
Which expression is equivalent to
(5^-2)(5^-1)
-1/125
-1/5
1/125
1/5
Answer:
1/5
Step-by-step explanation:
Answer:
D
Step-by-step explanation:
In two or more complete sentences explain how to balance the chemical equation and classify its reaction type. ___NaI + ___Pb(SO4)2 ⟶ ___PbI4 + ___Na2SO4
Answer:
4112
Step-by-step explanation:
Answer:
By applying law of conservation of mass.
Explanation:
Every balanced chemical equation follows law of conservation of mass.
This law states that mass can neither be created nor can be destroyed but it can only be transformed from one form to another form.
This law also states that the total number of individual atoms on the reactant side must be equal to the total number of individual atoms on the product side.
For the given reaction, the balanced chemical equation follows:
4Na1+Pb(SO4)__Pb14+2Na2SO4
On reactant side:
Number of sodium atoms = 4
Number of iodine atoms = 4
Number of lead atoms = 1
Number of sulfur atoms = 2
Number of oxygen atoms = 8
On product side:
Number of sodium atoms = 4
Number of iodine atoms = 4
Number of lead atoms = 1
Number of sulfur atoms = 2
Number of oxygen atoms = 8
Hence, the balanced chemical equation is written above.
Step-by-step explanation:
Which statement is the lie?
Part A: Prompt: \large 4n-3
A. Three less than four times a number
B. Four times a number less than 3
C. Four times a number decreased by 3
Answer:
C. Four times a number decreased by 3
Here is a system of linear equations:
equation 1: 2x + 7y = 8
equation 2: 2x + y=14
Solve this system with either the substitution method
OR the elimination method. Type your answer as an
ordered pair, then explain how you found the solution to
the system.
Answer:
X=7.5 y=-1
Step-by-step explanation:
[tex]2x + 7y = 8 \\ 2x + y = 14[/tex]
I multiplied the equation with - 1 to than I sum it with the second one to get rid of x
[tex] - 6y = 6 \\ y = - 1[/tex]
Now you put Y in on of the equation and you get x.
[tex]2x - 1 = 14 \\ 2x = 15 \\ x = 7.5[/tex]
16/17 rounded to the nearest hundredth
Answer:
0.941
Step-by-step explanation:
Triangle PQR is similar to triangle VWX. What is the length of PR?
Answer:10.5
Step-by-step explanation:I’m smart
Answer: 10 i promise u it is.
Step-by-step explanation:
what is the equation for 15% of 24
Answer:
5 / 5 = 100% Nov 18 11:54 UTC (GMT)
15 / 24 = 62.5% Nov 18 11:54 UTC (GMT)
255 / 280 = 91.071428571429% Nov 18 11:54 UTC (GMT)
0.067 = 6.7% Nov 18 11:54 UTC (GMT)
51 / 50 = 102% Nov 18 11:54 UTC (GMT)
Answer:
24 times .15
Step-by-step explanation:
15% is equal to .15, and in this case, if you are trying to find the answer, it is 3.6
Identify a and b for the hyperbola with equation. (y^2/b^2)-(x^2/a^2)=1
The value of (a) and (b) for the hyperbola are [tex]\sqrt 3[/tex] and 2
The equation of the hyperbola is given as:
[tex]\frac{y^2}{b^2} - \frac{x^2}{a^2} = 1[/tex]
The curve of the graph passes through points (0,2) and (-4,3).
So, we have:
[tex]\frac{2^2}{b^2} - \frac{0^2}{a^2} = 1[/tex] and [tex]\frac{(-4)^2}{b^2} - \frac{3^2}{a^2} = 1[/tex]
[tex]\frac{2^2}{b^2} - \frac{0^2}{a^2} = 1[/tex] becomes
[tex]\frac{4}{b^2} = 1[/tex]
Cross multiply
[tex]b^2 = 4[/tex]
Take positive square root of both sides
[tex]b = 2[/tex]
[tex]\frac{(-4)^2}{b^2} - \frac{3^2}{a^2} = 1[/tex] becomes
[tex]\frac{(-4)^2}{2^2} - \frac{3^2}{a^2} = 1[/tex]
[tex]\frac{(-4)^2}{4} - \frac{9}{a^2} = 1[/tex]
[tex]4 - \frac{9}{a^2} = 1[/tex]
Collect like terms
[tex]- \frac{9}{a^2} = -3[/tex]
Cross multiply
[tex]-3a^2 = -9[/tex]
Divide both sides by -3
[tex]a^2 = 3[/tex]
Take square roots of both sides
[tex]a = \sqrt 3[/tex]
Hence, the value of (a) and (b) for the hyperbola are [tex]\sqrt 3[/tex] and 2
Read more about hyperbolas at:
https://brainly.com/question/14503968
Which equation is parallel to
y =2/3x – 6 and passes through (9, -3)?
Answer:
y=2/3x -3
Step-by-step explanation:
y=mx+c
If the gradient(m) is the same then it's parallel.
The line passes through -3 so the y intercept(c) is -3
Answer:
Y=2/3x-9
Step-by-step explanation:
Y=mx+c
y=2/3x+c
Then substitute the coordinates
y=-3
x=9
-3=2/3*(9)+c
-3=6+c
Make c the subject by subtracting 6 from both sides.
-9=c
so the answer is
Y=2/3x-9
(Blank) Divided by 4 = 8 Remainder 3
I NEED HELP ASAP!!PLEASE HELP ME WITH MY MATH!
Answer:
A. -2, 9
B. -2, 4
C. -8, 4
D. -8, 9
Write out the form of the partial fraction decomposition of the function (as in this example). A) x4 − 2x3 + x2 + 2x − 1/x2 − 2x + 1B) x2 - 1/x3 + x2 + x
Answer:
A. [tex]\mathbf{\dfrac{x^4-2x^3+x^2+2x-1}{x^2-2x+1 }= x^2 + \dfrac{A}{x-1}+ \dfrac{B}{(x-1)^2}}[/tex]
B. [tex]\mathbf{\dfrac{x^2-1}{x(x^2+x+1)} = \dfrac{A}{x}+ \dfrac{Bx+C}{x^2 +x+1}}[/tex]
Step-by-step explanation:
A.
Given that:
[tex]\dfrac{x^4 -2x^3 +x^2+2x -1}{x^3 -2x +1}[/tex]
[tex]\dfrac{x^4 -2x^3 +x^2+2x -1}{x^3 -2x +1} =\dfrac{(x^4 -2x^3+x^2) +(2x-1)}{x^3 -2x +1}[/tex]
[tex]=\dfrac{(x^4 -2x^3+x^2)}{x^3 -2x +1} + \dfrac{(2x-1)}{x^3 -2x +1}[/tex]
[tex]= \dfrac{x^2(x^2-2x+1)}{x^2-2x+1}+ \dfrac{2x-1}{(x-1)^2}[/tex]
[tex]\dfrac{x^4-2x^3+x^2+2x-1}{x^2-2x+1 }= x^2 + \dfrac{2x-1}{(x-1)^2}---(1)[/tex]
Further, the partial fraction decomposition of [tex]\dfrac{2x-1}{(x-1)^2}[/tex] can be written as:
[tex]\dfrac{2x-1}{(x-1)^2} = \dfrac{A}{x-1}+ \dfrac{B}{(x-1)^2}[/tex]
From equation one, replacing the values; we have the partial fraction decomposition of the function to be:
[tex]\mathbf{\dfrac{x^4-2x^3+x^2+2x-1}{x^2-2x+1 }= x^2 + \dfrac{A}{x-1}+ \dfrac{B}{(x-1)^2}}[/tex]
B.
Given that:
[tex]\dfrac{x^2-1}{x^3+x^2+x}[/tex]
[tex]\dfrac{x^2-1}{x^3+x^2+x} = \dfrac{x^2-1}{x(x^2+x+1)}[/tex]
Therefore, the partial fraction of decomposition is:
[tex]\mathbf{\dfrac{x^2-1}{x(x^2+x+1)} = \dfrac{A}{x}+ \dfrac{Bx+C}{x^2 +x+1}}[/tex]